The girl who drank the moon - Barnhill, Kelly Regan (Algonquin Young Readers, 2016)
"An epic fantasy about a young girl raised by a witch, a swamp monster, and a Perfectly Tiny Dragon, who must unlock the powerful magic buried deep inside her"-- Provided by publisher.